Homestead : the series Season 1 [videorecording (DVD)] - Ross, Jason; Kasica, Ben (Angel Studios, 2026)
After a nuclear bomb detonates off the coast of Los Angeles, a cone-pampered nation devolves into brutal chaos. The series follows the survivors within the Homestead as they clash against one another and the violent world outside. Are they an ark or a fortress? Is it kill-or-be-killed, or is God doing something greater?